Postcolonial intellectuals: new paradigms. - Ponzanesi, Sandra (Postcolonial Studies, 2021)
The article presents the discussion on embedding in collective discursive practices and political engagements. Topics include referring to the role of publicness and democratic influence, philosophy, concerning the question of truth and gender studies; and attributes such as charisma, popularity and fandom often approaching the realms of celebrity and star status.